Poetics and Singing of Decima in the Orality of Caripe - Mostacero, Rudy (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Orality is characterized by its historical, social, and cultural relevance. Despite technological innovations, orality has not been displaced; on the contrary, it has been reinterpreted. The purpose of this article is to present the originality and richness of oral literature in the community of Caripe El Guácharo, Venezuela. It will explain the historical and social context of the eastern “galerón”, the fusion of two cultural traditions, and the impact that Greek mythology has had on the repertoire of its singers. Participative action research and case study were used to obtain the data, which was then analyzed qualitatively. It is concluded that the “décima cantada” has been related to religiosity, to peasant activities, and within one historical alternative of having started as a memorized singing and ended up being an improvised singing.